2003
DOI: 10.1021/ja028362p
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ortho C−H Activation of Haloarenes by an Ir(I) System

Abstract: The cationic PNP-Ir(I)(cyclooctene) complex 1 (PNP = 2,6-bis-(di-tert-butyl phosphino methyl)pyridine) reacts with benzene at 25 degrees C to quantitatively yield the crystallographically characterized, square pyramidal, iridium phenyl hydride complex cis-(PNP)Ir(Ph)(H), 2, in which the hydride is trans to the vacant coordination site. The cationic complex 2 is stable to heating at 100 degrees C, in sharp contrast to the previously reported unstable neutral, isoelectronic (PCP)Ir(H)(Ph) (PCP = eta(3)-2,6-((t)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 17 publications
(21 reference statements)
4
94
1
3
Order By: Relevance
“…After 1-h reaction times, mixtures of ortho-, meta-and parahalo or -methoxy complexes are observed, and after 24-48 h, most of the mixtures equilibrate toward the ortho isomer, whose substituent is coordinated to the iridium center (13). Table 2 summarizes the Milstein results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 1-h reaction times, mixtures of ortho-, meta-and parahalo or -methoxy complexes are observed, and after 24-48 h, most of the mixtures equilibrate toward the ortho isomer, whose substituent is coordinated to the iridium center (13). Table 2 summarizes the Milstein results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports that are highly relevant to our mechanistic speculations, but that highlight a more fundamental problem, are the selective ortho C-H activation of haloarenes and anisole by an iridium(I) complex. 13 In this chemistry, complex 11 reacts directly with the substrates to give the aryl hydrido complexes 12 ( Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…[69] Weiterhin wurde die erste selektive ortho-C-H-Aktivierung von Halogenarenen unter Verwendung derselben Vorstufe beschrieben (Schema 17). Während die Reaktion mit Fluorbenzol nicht regioselektiv verläuft, konnten ortho/meta/paraSelektivitäten von ca.…”
Section: Iridiumunclassified
“…These PNP pincer ligands have given rise to remarkable results in a variety of chemical transformations (Figure 1). [3,4] The first monoanionic example of this class of ligands (A) was synthesized by Sacconi and co-workers in the late sixties, [5] and more recently, its late-transitionmetal complexes have received increasing attention. [6] Fryzuk and co-workers extensively studied an amido ligand with a SiMe 2 CH 2 backbone (B), the early-transition-metal complexes of which have given rise to remarkable patterns of reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Treatment of this complex with chlorobenzene led to selective ortho C-H activation. In recent work, Ozerov and co-workers reported that for PhCl and PhBr the product of C-Hal oxidative addition to [(PNP)Ir] is thermodynamically favored over the products of C-H oxidative addition but due to the high activation barrier is only kinetically accessible at high temperatures.…”
Section: Introductionmentioning
confidence: 99%